PENGARUH RISIKO TERHADAP KINERJA PASAR INDUSTRI BARANG KONSUMSI DI INDONESIAPENGARUH RISIKO TERHADAP KINERJA PASAR INDUSTRI BARANG KONSUMSI DI INDONESIA: Kathleen Arlen Manueke - Kathleen Arlen Manueke (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2023)
This research is conducted to test the impact of risk on market performance using consumer goods industry companies’ secondary data listed on the Indonesia Stock Exchange for the years 2014-2018. The results show that risk which is measured by the beta has a positive significant impact on the market performance based on the price-earnings ratio measurements.  In addition, the risk that is measured by the debt-to-equity ratio has a significantly positive impact on the market performance which is measured by price-to-book value. In terms of investment, however, the results of this study indicate that Indonesian goods industry investors do not consider to the level of market risk only, but they look at the credit risk. This suggests that investors dare to take high risks to gain high returns.